Faktor-Faktor Yang Mempengaruhi Produksi Telur Itik Dan Strategi Pengembangan Usaha Ternak Itik Di Kabupaten Merauke - yolanda Gebze; Ismoyowati Ismoyowati; Elly Tugiyani (Faculty of Agriculture, Musamus University, 2020)
Ducks are one type of waterfowl that has advantages, namely the stage of disease, fast growth and being able to digest high crude fiber. The purpose of this study is: The purpose of this study was to analyze the factors that influence egg production and business development strategies for duck farming. The research method used was observation, questionnaire, interview with sampling of 50 respondents. Data were analyzed by tabulation and discussed in a descriptive manner. The analysis used descriptive analysis is a research method that takes a sample from the population and uses a questionnaire as a tool to collect data. Data analysis techniques using the Cobb Douglas function. The results showed that the production of duck eggs in Merauke Regency was still low and showed an increase in production from year to year. Factors of the production of the amount of feed and the number of livestock simultaneously had a positive and significant effect on the results of egg production partially. Ducks livestock development strategies in Merauke Regency include: (1) Increasing knowledge and skills of breeders regarding alternative feeding for ducks (azolla sp and onggok), (2) Utilizing existing potential (agricultural waste) as a source of feed, (3) Providing extension agents of good farming practices and good management, (4) Implement post-harvest management and management to produce good quality eggs.